2014
DOI: 10.1016/j.geomorph.2013.08.009
|View full text |Cite
|
Sign up to set email alerts
|

One million cubic kilometers of fossil ice in Valles Marineris: Relicts of a 3.5Gy old glacial landsystem along the Martian equator

Abstract: Self-consistent landform assemblages suggest that Valles Marineris, the giant valley system that stretches along the Martian equator, was entirely glaciated during Late Noachian to Early Hesperian times and still contains huge volumes of fossil ice. Some of these glacial landform assemblages are illustrated here, with representative examples selected in three regions: Ius Chasma, Central Candor Chasma and the junction between Coprates Chasma and Capri Chasma. A morphological boundary separating an upper spur-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 132 publications
(239 reference statements)
3
64
0
Order By: Relevance
“…Ice could have been present from the initial formation of the ILDs (Michalski and Niles, 2012), from a previous glacial system in Valles Marineris (Gourronc et al, 2014), or more recent obliquity-driven processes (Madeleine et al, 2009). Sublimation of ice on Mars is a complex process that depends heavily on as doi:10.1130/G35790.1 Geology, published online on 29 July 2014 parameters such as ambient and surface temperature, regolith diffusion properties, and wind (Williams et al, 2008).…”
Section: Ice Sublimationmentioning
confidence: 99%
“…Ice could have been present from the initial formation of the ILDs (Michalski and Niles, 2012), from a previous glacial system in Valles Marineris (Gourronc et al, 2014), or more recent obliquity-driven processes (Madeleine et al, 2009). Sublimation of ice on Mars is a complex process that depends heavily on as doi:10.1130/G35790.1 Geology, published online on 29 July 2014 parameters such as ambient and surface temperature, regolith diffusion properties, and wind (Williams et al, 2008).…”
Section: Ice Sublimationmentioning
confidence: 99%
“…This is possible only if the friction has diminished quite dramatically during the flow, which is consistent with ice lubrication . According to recent work by Gourronc et al (2014), some features in Valles Marineris are compatible with a full glacial regime. However, exposed ice in the form of a glacier might be problematic in terms of thermodynamical stability of ice on equatorial Mars; moreover, the deposits would have been displaced by subsequent ice flow (De Blasio 2011a).…”
Section: Discussionmentioning
confidence: 94%
“…Mars has unquestionably been wetter and icier than today during part of its history (e.g., Baker 2001;Kargel 2004;Squyres et al 2004;Carr 2006;Fairén 2010;Parker et al 2010). Whereas the surface of the lowlands in the northern hemisphere exhibits widespread indications of ice at higher latitudes (Mouginot et al 2012), only more recently has it been suggested that glacial conditions might have been achieved in the equatorial regions during some episodes of Mars Hesperian-Amazonian history (Head and Marchant 2003;Murray et al 2005;Fueten et al 2011;De Blasio 2011a;Gourronc et al 2014). Thus, different lines of evidence suggest that VM has been filled for a long period by subsurface or exposed ice (De Blasio 2011a;Gourronc et al 2014) or a lake (Ori et al 2000;Chapman 2008, 2010;Lucchitta 2009;Metz et al 2009;Flahaut et al 2010;Lucchitta 2010;Sowe et al 2011;Warner et al 2013;Fueten et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, the Antarctic and Greenland ice sheets have approximate volumes of 26 × 10 6 and 3 × 10 6 km 3 respectively (Marshall, 2005), while the present-day Martian North and South Polar Caps have approximate volumes of 1.5 × 10 6 and 2.5 × 10 6 km 3 respectively (Smith et al, 1999). Volumes on the order of 10 6 to 10 7 km 3 have been proposed for paleoglaciers on the Tharsis dome, in Valles Marineris, in Dorsa Argentea and in Deuteronilus Mensae (Kite and Hindmarsh, 2007;Fastook et al, 2008Fastook et al, , 2011Fastook et al, , 2012Gourronc et al, 2014). The ice sheet simulated here in Isidis Planitia thus stands in the range of volumes suggested for other martian paleo-glaciers, but it is nearly twice as large as the total volume of ice trapped in the present-day polar caps.…”
Section: Extent Thickness and Volume Of Ice Sheetmentioning
confidence: 99%
“…old) glaciations has been described at all latitudes (Squyres, 1978(Squyres, , 1979Head and Marchant, 2003;Head et al, 2005Head et al, , 2006aHead et al, , 2006bHead et al, , 2010Shean et al, 2005Shean et al, , 2007Shean, 2010;Garvin et al, 2006;Milkovich et al, 2006;Levy et al, 2007Levy et al, , 2010Dickson et al, 2008Dickson et al, , 2010Holt et al, 2008;Kadish et al, 2008;Morgan et al, 2009;Fassett et al, 2010;Souness et al, 2012;Hubbard et al, 2014). There is also a growing body of geomorphic evidence in support of earlier glaciations, during the Hesperian (3-3.7 Ga) and perhaps during the Noachian (>3.7 Ga) (Howard, 1981;Kargel and Strom, 1992;Kargel et al, 1995;Head and Pratt, 2001;Milkovich et al, 2002;Ghatan and Head, 2004;Mège and Bourgeois, 2011;Fastook et al, 2012;Gourronc et al, 2014).…”
Section: Introductionmentioning
confidence: 99%